Positive illusions and the temptation to borrow - Eva Kløve; Halvor Mehlum (University of Oslo, Department of Economics, 2017)
We provide an explanation of the low willingness to save that is observed in many poor countries. Our explanation is based on the hypothesis that people have an over-optimistic outlook. As discussed in the psychological literature, an illusionary positive view of the future may be a good thing. However, we show that it can lead individuals to accumulate unsustainable levels of debt. Using survey data from South Africa, we confirm that poor people are indeed overly optimistic, and also that optimism is positively and significantly related to debt accumulation.
Keywords: D03; D14; O1; O12; 330; poverty; savings; discounting; debt